Criminal acts related to poaching in Kazakhstan: a study of the offender’s personality - Zholzhaxynov, Zh.B.; Sadvakassova, A.T. (Karagandy University of the name of academician E.A. Buketov, 2025)
This study presents a comprehensive criminological analysis of the personality of poachers who commit criminal offenses in the field of illegal nature management in the territory of the Republic of Kazakhstan. The purpose of the study is to identify a set of demographic, social, criminal-legal and psychological characteristics of offenders, as well as to determine the factors predisposing to the commission of poaching. The methodological basis of the study was statistical and substantive analysis, methods of interviewing, questionnaires, grouping and expert assessments. As a result of the conducted study, it was established that the main group of poachers consists of men of working age (30–39 years old), who do not have higher education and often do not have official employment. It was determined that the main motivational determinants of their criminal activity are economic necessity, lack of environmental awareness and social disorder. In addition, the analysis of empirical data allowed us to identify characteristic behavioral attitudes and the level of legal awareness of offenders. Special attention is paid to the comparative analysis of Kazakhstan and international practice, including the study of gender, age and educational differences among poachers. Conclusions are made about the need to introduce comprehensive preventive measures aimed at reducing the level of poaching, as well as the development of targeted programs for the formation of environmental culture and social responsibility of the population.
Қазақстандағы браконьерлік саласындағы қылмыстық жазаланатын іс-әрекеттер: құқық бұзушының жеке басын зерттеу
Уголовно-наказуемые деяния в сфере браконьерства в Казахстане: исследование личности правонарушителя
Keywords: poaching; criminal offense; environmental crime; personality of the offender; demographic factors; environmental legal consciousness; statistical analysis; legislation; crime prevention; illegal use of natural resources